Hubungan Antara Usia dan Paritas Ibu Bersalin dengan Bayi Berat Lahir Rendah (BBLR) di Rumah Sakit Islam Siti Khadijah Palembang - ANNISA KHOIRIAH (Jurnal Kesehatan, 2017)
Low Birth Weight is the birth weight of 1,500-2,500 grams. According to the data of Siti Khadijah Palembang Islamic Hospital in 2016 babies born in LBW from January to September of 2016 both live and die amounted to 172 babies from 1,000 births. The purpose of this study is to know the relationship between maternal age and parity with low birth weight babies at Siti Khadijah Palembang Islamic Hospital in 2016. The method used is an analytical survey with cross sectional approach. The population in this study is all mothers of maternity in Islamic Hospital Siti Khadijah Palembang in 2016 with a sample of 91 people. Based on the univariate analysis of 91 respondents who are not BBLR of 64.8%, low risk as much as 53.8%, low parity 54.8%. The result of bivariate analysis of low risk age that gave birth to LBW was 20,4%, low parity giving birth of LBW by 24%. Age of mother get p value 0,003 <0,05, parity of mother get p value 0,025 <0,05. There is a relationship between maternal age and parity with LBW. For the institution, it is expected that the results of this study can provide benefits for students about the relationship between maternal age and parity with Low Birth Weight. Hospital Parties can provide more intensive information and counseling to the community about the age and parity relationship of delivery mothers with low birth weight babies.